Inkonsistensi Penjatuhan Sanksi Pidana terhadap Pengguna Narkotika dalam Praktik Peradilan - Qothrunnada Syahira Ramadiani; Waluyadi Waluyadi; M. Noupel M. Noupel (Jurnal Hukum Lex Generalis, 2026)
This study aims to analyze the judge's considerations and the inconsistency of sanctions imposed on narcotics users in Decision Number 75/Pid.Sus/2025/PN Cbn and Decision Number 500/Pid.Sus/2018/PN Jkt.Sel. The study uses a normative juridical method with a statutory approach and a case approach. The results of the study indicate that both defendants were proven to be narcotics abusers for themselves based on Article 127 paragraph (1) letter a of Law Number 35 of 2009 concerning Narcotics, but were given different sanctions, namely imprisonment and rehabilitation. Therefore, the Supreme Court needs to formulate more specific guidelines regarding the parameters for imposing rehabilitation for narcotics users in order to achieve consistency in decisions